2003
DOI: 10.1016/s0304-8853(02)01171-x
|View full text |Cite
|
Sign up to set email alerts
|

Possible magnetic phase separation in Ru-doped La0.67Ca0.33MnO3

Abstract: Abstract:X-ray diffraction, resistivity, ac susceptibility and magnetization studies on La 0.67 Ca 0.33 Mn 1-x Ru x O 3 (0 ≤ x < 0.1) were carried out. A significant increase in the lattice parameters indicated the presence of mixed valance state of Ru: Ru 3+ and Ru 4+. The resistivity of the doped compounds exhibited two features: a broad maximum and a relatively sharp peak. While a para to ferromagnetic transition could be observed for the latter peak, no magnetic signal either in ac susceptibility or in mag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 54 publications
2
26
0
Order By: Relevance
“…We have attempted to substitute Sb 5+ ion on the Mn-site in Pr 2/3 Ba 1/3 MnO 3 (PBMO) material because of its ionic size compatibility in six-fold co-ordination (0.60Å) to that of Mn 3+ /Mn 4+ ions (0.645Å and 0.53Å, respectively). Pr 2/3 Ba 1/3 MnO 3 material has been chosen because it shows, besides the usual higher temperature I-M transition, a second peak in its ρ-T behaviour at lower temperature which is ascribed to the ionic size mismatch [15,16] and is not due to the presence of a second phase like those reported earlier [17,18]. Such a material with Sb doping is interesting because of the higher ionic size mismatch between the ions present at the rare-earth site.…”
Section: Introductionmentioning
confidence: 95%
“…We have attempted to substitute Sb 5+ ion on the Mn-site in Pr 2/3 Ba 1/3 MnO 3 (PBMO) material because of its ionic size compatibility in six-fold co-ordination (0.60Å) to that of Mn 3+ /Mn 4+ ions (0.645Å and 0.53Å, respectively). Pr 2/3 Ba 1/3 MnO 3 material has been chosen because it shows, besides the usual higher temperature I-M transition, a second peak in its ρ-T behaviour at lower temperature which is ascribed to the ionic size mismatch [15,16] and is not due to the presence of a second phase like those reported earlier [17,18]. Such a material with Sb doping is interesting because of the higher ionic size mismatch between the ions present at the rare-earth site.…”
Section: Introductionmentioning
confidence: 95%
“…In this context, role of Mn-site substitutions on the electrical as well as the magnetotransport properties should be studied within the framework of mixed phase tendency. In the process of understanding the role of local structure due to the modified ionic size at the Mn site as well as the local magnetic coupling on the ground state properties of CMR manganites, we have carried out diamagnetic (Al 3+ , Ga 3+ , Ti 4+ , Zr 4+ and Hf 4+ ) as well as paramagnetic (PM) substitutions (Fe 3+ and Ru 4+ ) at the Mn site of La 0.67 Ca 0.33 MnO 3 , a canonical example of intermediate bandwidth CMR manganites [27][28][29][30]. It is found that all substitutions suppress the transition temperatures to different extent and eventually modify the ferromagneticmetallic (FM-M) ground state to a cluster glass (CG).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Ru substitution results in two metal-insulator transitions 32 (MITs) both exhibiting peaks in the magnetoresistance.…”
mentioning
confidence: 99%
“…67 Ca 0.33 MnO 3 compounds, ρ o increases by a factor of 5. 32 Also in the case of electronic phase separation, only a single maximum in the resistivity curves is expected, since out of the two phases, the FM phase alone is metallic in nature. Thus it is concluded that the phase separation encountered in Ru substituted La 0.67 Ca 0.…”
mentioning
confidence: 99%
See 1 more Smart Citation